2013
DOI: 10.2225/vol16-issue6-fulltext-14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in Kalanchoe daigremontiana leaves during plantlet formation under drought stress

Abstract: Background:Kalanchoe daigremontiana is an attractive model system for the study of the molecular mechanisms of somatic embryogenesis and organogenesis competence due to its formation of plantlets with adventitious roots on the leaf margins that are derived from somatic embryos. The suppression subtractive hybridization technique was used to investigate gene expression during asexual reproduction. Leaves from plants subjected to drought stress provided the source of 'Tester' DNA, and leaves from plants grown un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…In terms of the functions of these genes, most of them are involved in regulating and sensing biotic and abiotic stress (Table S3). This observation is predictable as the rate of plantlet formation in K. daigremontiana is enhanced by drought stress [25]. Additionally, few plants developed a preference for asexual reproduction under certain stress conditions [3].…”
Section: Discussionmentioning
confidence: 81%
“…In terms of the functions of these genes, most of them are involved in regulating and sensing biotic and abiotic stress (Table S3). This observation is predictable as the rate of plantlet formation in K. daigremontiana is enhanced by drought stress [25]. Additionally, few plants developed a preference for asexual reproduction under certain stress conditions [3].…”
Section: Discussionmentioning
confidence: 81%
“…Suppression subtractive hybridization studies revealed that the overexpression of a large number (390) of unigenes in the asexual reproduction of K . daigremontiana (Zhong et al, 2013). Figure 1B highlights common cellular and molecular events in different stages of transition from somatic to embryogenic cell fate.…”
Section: Differentiation Of Embryos or Plantlets From Vegetative Orgamentioning
confidence: 99%
“…Sin embargo, el efecto de sus extractos en las células cancerosas solo se probó en las células T de leucemia linfoblástica humana [3]. En China, K. daigremontiana se ha utilizado durante cientos de años tanto por vía oral como tópica para tratar afecciones como el vómito sanguíneo, quemaduras y cuadros gripales [15]. Tradicionalmente, las infusiones o decocciones de sus hojas son utilizadas como tratamiento alternativo para distintas dolencias como fiebre, hipertensión, relajante muscular, sedante, antihistamínico, entre otros [10].…”
Section: Introductionunclassified
“…Recientemente, K. daigremontiana se ha convertido en una fuente de nuevos compuestos para el tratamiento de tumores y enfermedades inflamatorias y alérgicas [15]. Se aislaron esteroides cardiotónicos bufadienólidos de K. daigremontiana, los cuales presentaron efectos inhibitorios sobre un tipo de virus (Epstein-Barr) que ataca los linfocitos B y se asocia con el desarrollo de muchas clases de neoplasia.…”
Section: Introductionunclassified